Foundation of multinational financial management - Shapiro, Alan C. (Wiley, 2005)
All too often, companies focus on the threats and risks inherent in venturing abroad. But multinational firms actually have unique opportunities that are not available to purely domestic firms. Now updated, revised, and reorganized, Alan Shapiro’s Foundations of Multinational Financial Management, 5/e will help you take advantage of these valuable opportunities. Foundations emphasizes broad concepts and practices and provides a clear conceptual framework for analyzing key financial decisions in multinational firms. The text treats international financial management as a natural and logical extension of the principles learned in the foundations course in financial management.